Research into Quality Management and Social Responsibility - Tarí, Juan José (2011)
This article presents a systematic literature review on quality management and social responsibility (focusing on ethical and social issues). It uses the literature review to identify the parallels between quality management and social responsibility, the extent to which qualitative, quantitative and mixed methods are used, the countries that have contributed most to this area, and how the most common quality management practices facilitate social responsibility. The literature review covers articles about quality management and social responsibility (focusing on ethical and social categories) based on a computer search in three databases, namely ABI Inform, Emerald and Science Direct, and includes articles dealing with the subject that were found in the lists of references of the articles found in the primary search, as well as a search in six top management journals. The results show (1) the journals most likely to publish this type of article; (2) the range of qualitative, quantitative and mixed methods used; (3) the most productive countries in this field; (4) the parallels between quality management and social responsibility; and (5) how the most common quality management practices facilitate ethical behaviour and social aspects.
Keywords: Systematic literature review; Social Responsibility; quality practices; Quality Management